How Can Jurisdictional Approaches to Sustainability Protect and Enhance the Rights and Livelihoods of Indigenous Peoples and Local Communities? - DiGiano, Maria; Stickler, Claudia; David, Olivia (Frontiers in Forests and Global Change, 2020)
Tropical forests are posited to hold up to one-third of the solution to slow climate change. It is estimated that over two-hundred million “forest peoples”- including indigenous peoples and local communities- live within and depend upon the tropical forests in the Amazon, Southeast Asia, Mesoamerica and the Congo Basin. To successfully mitigate climate change, we must find new forms of collaboration that meet the goals of forest-dependent communities for secure land rights, equitable participation in decision-making, and dignified livelihoods in conjunction with meeting commitments to reduce GHG emissions. In 2018, 34 subnational governments and 18 indigenous and local community organizations announced their endorsement of the “Guiding Principles for Collaboration between Subnational Governments, Indigenous Peoples and Local Communities”. The Guiding Principles of Collaboration (GPC) are a set of 13 universal tenets, which lay out a blueprint for collaboration between subnational state actors, indigenous peoples and local communities to recognize rights, support livelihoods, strengthen participation of forest-dependent communities in decision-making, and protect indigenous and community environmental defenders within the context of joint action for climate change mitigation. Their implementation would advance the integration of climate justice in subnational efforts for forest conservation. Taking the GPC as a departure point, we explore how approaches to jurisdictional sustainability can protect and enhance the rights and livelihoods of Indigenous Peoples (IP) and Local Communities (LC). We develop and apply a suite of indicators to assess existing conditions across 11 tropical forest jurisdictions towards meeting the commitments described in the GPC. Our findings suggest that while Indigenous Peoples and Local Communities rights are recognized within national legal frameworks, implementation and security of those rights is uneven across subnational jurisdictions. Participation of IP and LC is not yet formalized as part of jurisdictional climate change mitigation initiatives in most cases, limiting their potential inform policy outcomes and benefit-sharing mechanisms. Monitoring the implementation of the GPC may foster greater accountability for commitments, as well as collective action and learning to support regional transformations to sustainability.